The Research on Analysis of Rural Industry Brand Characteristics and Creative Design Strategies in Fengxian District of Shanghai - Zhou, Jianan; Puntien, Pisit; Dumrongsatian, Sompol (Journal of Roi Kaensarn Academi, 2024)
The accelerated pace of urbanization, rural areas confront challenges including sluggish economic growth, population decline, and the deterioration of traditional industries. To address these challenges and promote the sustainable development of rural industries, this study focuses on Fengxian District in Shanghai, conducting an analysis of rural industry brand characteristics and creative design strategies. This study aimed to investigate the characteristics of industry brands and develop creative design strategies in Fengxian District, Shanghai. The samples of this study were 65 participants that were obtained from purposive sampling. The research instruments were the questionnaires and the interviews. This research employs a mixed-methods approach, primarily qualitative, integrating materials. The data from the questionnaires was analyzed using 1) descriptive statistics and 2) content analysis for qualitative data from the interview. The findings revealed two key results as follows: 1) Fengxian District’s rural industry brand is distinguished by its natural, green, and local attributes, and 2) The creative design strategy involves using Fengxian yellow peaches as a case study, deeply exploring and inheriting cultural resources, integrating natural landscapes and ecological concepts, and utilizing innovative design and artistic expression to develop brand IP and marketing strategies. The proposed creative design strategy, as outlined in this study, not only offers a concrete implementation plan for the development of the rural industry brand in Fengxian District but also serves as a valuable reference for rural brand building in other regions. Moreover, these results contribute to promoting the sustainable development of rural industries in Fengxian District, assist in achieving the goal of rural revitalization, and offer theoretical support and practical guidance for Chinese rural industries to establish a unique brand image in the context of globalization.